Peran Inflasi dalam Memoderasi Pengaruh Rasio Keuangan terhadap Harga Saham - Alwyah, Lila; Arfatun, Arfatun (Politeknik Ganesha Medan, 2024)
Public company stock prices are an important research problem to study. Prior to investing in a company, it's crucial for investors to analyze its financial ratios. This study aims to gather empirical evidence on how inflation moderates the efect of financial ratios such as Current Ratio (CR), Debt to Equity Ratio (DER), Price Earning Ratio (PER), Return on Assets (ROA), and Return on Equity (ROE) on stock prices. The sample selection employed a purposive sampling method, the criteria used as a basis were (1) companies listed on the IDX and consistently included in the LQ45 Index from 2021 to 2023, and (2) No data is missing as a result of this process, 24 companies were chosen as samples, resulting in 72 sample observations. Results indicate that ROA influences stock prices in a positive direction, while ROE influences stock prices in a negative direction. The variables CR, DER, and PER were found not to influence stock prices. Inflation was observed to moderate the effects of DER, ROA, and ROE on stock prices, while not affecting the influence of CR and PER on stock prices. Additionally, inflation was identified as a pure moderator in this context. This study underscores the intricate interplay between financial ratios, inflation, and stock prices, providing valuable insights for investors and researchers alike.